Pragmatic Basis for Utilitarian Evaluation in German Engineering Discourse - N. Ju. Shnyakina; A. M. Klyoster (Дискурс профессиональной коммуникации, 2023)
This paper investigates how engineering discourse evaluates technical developments based on their utility, uselessness, or harm. It examines German-language specialized texts that report on contemporary scientific innovations, using a functional-pragmatic analysis method to explore the propositional structure of statements that convey utilitarian information. The article, published in a scientific journal, is considered in this study as a situationally conditioned speech act that aims to inform readers through the communicative strategy of explanation. The analysis focuses on identifying the implicit configurations that the author creates in the linguistic expression of propositions such as “fact,” “opinion,” and “assessment.” The combination of these propositions in one context allows describing the ways of presenting scientific data from a utilitarian point of view. Utilitarian evaluation mainly depends on the author’s explanation of cause-and-effect relationships, which form the basis for assessments. Moreover, the author often refers to authoritative opinions or experimental results to support the evaluation. The text also includes unargued assessments, which invite the reader to agree or disagree. The analysis in this paper shows that utilitarian assessments in engineering discourse are driven by the goal of professional communication. They follow the principles of rationality, provability, and objectivity, which are reflected in the author’s deliberate detachment from the subject of description. These pragmatic features are related to the values of professional communication, which involve not only providing reliable data but also promoting progressive ideas in society. The rhetorical effect of persuasion achieved by reasoned objectification of utilitarian assessments in the text is a distinctive characteristic of scientific discourse. It is also an efficient way of fulfilling the objectives of specialized communication. This study contributes to a better understanding of the pragmatic aspects of utilitarian evaluation in engineering discourse, highlighting its empirical basis and its importance for the wider field of professional communication.